Identification of an IRES within the coding region of the structural protein of human rhinovirus 16. Issue 6 (15th December 2021) - Shi, Bingtian; Song, Qinqin; Luo, Xiaonuan; Song, Juan; Xia, Dong; Xia, Zhiqiang; Liu, Mi; Wang, Wenjun; Wang, Ruifang; Du, Haijun; Wei, Qiang; Han, Jun
Abstract: As an alternative mechanism for cap‐dependent (m7GpppN) translation, internal ribosome entry site (IRES)‐dependent translation has been observed in the 5′ untranslated regions (5′ UTR) and coding regions of a number of viral and eukaryotic mRNAs. In this study, a series of 5′ terminal truncated structural protein genes that were fused with GFP was used to screen for potential IRESs, and IRESs were identified using a bicistronic luciferase vector or GFP expression vector possessing a hairpin structure. Our results revealed that a putative IRES was located between nt 1982 and 2281 in the VP3 coding region of the human rhinovirus 16 (HRV16) genomes. We also demonstrated that effective IRES‐initiated protein expression in vitro did not occur through splicing sites or cryptic promoters. We confirmed that thapsigargin (TG), an inducer of endoplasmic reticulum stress (ERS), facilitated increased IRES activity in a dose‐dependent manner. Additionally, the secondary structure of the IRES was predicted online using the RNAfold web server. Highlights: An IRES is found in the VP3 coding region of human rhinovirus 16. The IRES activity increased under endoplasmic reticulum stress.